Intracellular drug delivery: a route to more selective and effective treatments for disease - Mai, Quynh N. (2019)
The Neurokinin 1 receptor (NK1R) is a G protein-coupled receptor (GPCR) and member of the tachykinin family expressed in the central nervous system, immune cells, gastrointestinal tract and vascular endothelia. It is associated with neurogenic inflammation, gastrointestinal function and nociceptive transmission. Stimulation of NK1R by the endogenous agonist, substance P, initiates Gαq-mediated signalling, receptor phosphorylation and β-arrestin recruitment to initiate clathrin-dynamin mediated endocytosis. Internalised NK1R has a spatially and temporally dynamic signalling profile which has been demonstrated to underlie pathophysiological outcomes distinct from the plasma membrane. Therefore, endosomal NK1R populations may be considered a therapeutically distinct target. This thesis explores this concept, through the characterisation of NK1R signalling from endosomes, and the development of two novel drug delivery systems: 1) Lipid-conjugation to anchor soluble molecules into membranes and enhance their targeting; 2) pH-sensitive nanoparticles were used as a non-covalent method of packaging NK1R antagonists for targeted endosomal drug delivery.